Analysis and Design of QR Code Based Information System on Plant Identification - Ahmad Syaikhu; Rizky M. L. Soeryaprawira; Yoga A. Daswara; Cornelius Mellino Sarungu (IJNMT (International Journal of New Media Technology), 2022)
At the location of the environmental service dormitory in RW 04 Tegal Alur sub-district, Kalideres district, West Jakarta, the community cultivate various types of plants and there is a requirement to introduce or educate the public about types of plants and their benefits. The purpose of this research project is to analyze the needs, as well as to design the QR Code-based information system, especially in the process of educating the types of plants and their benefits in the area. The design process uses the object-oriented analysis and design (OOAD) method which explores UML modelling (use case, activity diagram, sequence diagram, class diagram). The analysis will be carried out on to be implemented business processes, then the results of the analysis are poured into the design of a QR code-based information system in the form of web and mobile app that can assist educational activities. Web application will be used by the administrator to manage data to be displayed in mobile app. Mobile app will be used by the user to explore plant species and their benefits based on QR code that installed near the plants.